Komunitas Historical Sumatera Utara dan Perannya dalam Mempromosikan Situs Islam di Sumatera Utara, 2016-2021 - Hasibuan, Yudi Pratama; Achiriah, Achiriah; Nurhayani, Nurhayani (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article aims to discuss the History of the Historical Community of North Sumatra and its role in promoting Islamic sites in North Sumatra. The North Sumatra Historical Community was established on January 17, 2016. This community is a community engaged in history, education, tourism and culture. The members of this community are approximately 20 people. The method used in this research is the historical method with four stages, namely; heuristics, criticism or verification, interpretation and historiography. Based on the results of research that the authors get. The efforts made by the Historical Community of North Sumatra in carrying out its role as an institution that promotes Islamic sites in North Sumatra are; holding seminars and discussions, being a tour guide, promoting various historical sites through social media.